Health Insurance Coverage and its Determinants among Middle-Income Households in Urban - Muhammad Aslam, Beenish Hafiz, Saba Parveen Soomro, Hafiz Muhammad Dawood, Akmal Khurshid Bhatti, Farhana, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Health insurance usually covers the expenditure during patient hospitalization. To achieve universal health coverage, it is mandatory to cover the middle-income groups under the government health insurance scheme. According to the review of literature, there is very limited knowledge present on health insurance and the factors determining its coverage among this group. Objective: The study was conducted to analyze the coverage of health insurance and its factors among the middle class households in urban areas. Study design: It is a community based study. This study was conducted on 210 participants attended the community medicine department of our hospitals for the duration of one year from November 2021 to October 2022. Material and Methods: The study was conducted on 210 participants. The written consent was taken from the participants and they were fully aware of the study. Interviews were conducted to find the issues and the point of view of clients and health insurance providers. It was also evaluated that what factors are liked by clients about the health insurance scheme. Results: There were three categories made to find the client’s perspective. One of them was lack of awareness. Then there were monetary issues. There were 28% participants that reported that they have recently insured themselves. There were 62% participants already insured in the past and 62% said that they have never insured themselves. Conclusion: Middle income families had better health insurance coverage than lower middle class. High premium charges, poor financial condition, lack of guidance, lack of knowledge about benefits of health insurance are some of the factors that lower the prevalence of health insurance. Keywords: Health insurance and financial condition.